2021
DOI: 10.1101/2021.09.29.462440
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loss of the cleaved-protamine 2 domain leads to incomplete histone-to-protamine exchange and infertility in mice

Abstract: Protamines are unique sperm-specific proteins that package and protect paternal chromatin until fertilization. A subset of mammalian species expresses two protamines (PRM1 and PRM2), while in others PRM1 is sufficient for sperm chromatin packaging. Alterations of the species-specific ratio between PRM1 and PRM2 are associated with infertility. Unlike PRM1, PRM2 is generated as a precursor protein consisting of a highly conserved N-terminal domain, termed cleaved PRM2 (cP2), which is consecutively trimmed off d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Defects in PRM2 processing were also described for histone variant H2A.L.2-KO, transition protein (TPs)-1 and -2 (TP1/TP2)-double KO, TP2-KO and cleaved PRM2 cP2-KO mouse models [40,[56][57][58], all of which display fertility problems. Interestingly, a recent study showed that mutation of a single non-arginine residue in PRM1 (P1 K49A/K49A ) leads to impaired PRM2 processing in mice [59].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Defects in PRM2 processing were also described for histone variant H2A.L.2-KO, transition protein (TPs)-1 and -2 (TP1/TP2)-double KO, TP2-KO and cleaved PRM2 cP2-KO mouse models [40,[56][57][58], all of which display fertility problems. Interestingly, a recent study showed that mutation of a single non-arginine residue in PRM1 (P1 K49A/K49A ) leads to impaired PRM2 processing in mice [59].…”
Section: Discussionmentioning
confidence: 99%
“…Arévalo et al have shown that mice lacking the highly conserved N-terminal part of PRM2, called cleaved PRM2 (cP2), display defective PRM2 processing and show a PRM1:PRM2 ratio of approx. 5:1 [40]. Mice lacking cP2 on one allele are infertile.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…P1 is expressed in its mature form, while P2 is initially expressed as a longer precursor (pro-P2) and undergoes selective proteolytic processing to produce its mature form (P2) once bound to DNA ( 88 , 89 ). Truncation of the amino terminus of P2, the portion of the protein that is typically cleaved (cP2) in the nucleus, causes infertility due to inefficient import of the protein into the nucleus, resulting in altered protamine ratios and immotile sperm; suggesting that the longer isoform may be required for protamine-chaperone interactions ( 90 ).…”
Section: Chromatin Dynamics During Spermatogenesis Lead To a Unique P...mentioning
confidence: 99%